Experimental investigation of specific heat capacity improvement of a binary nitrate salt by addition of nanoparticles/microparticles. (April 2019) - Liu, Ming; Severino, John; Bruno, Frank; Majewski, Peter
Highlights: Si3 N4 and SiC NPs have marginal effort on specific heat capacity of solar salt. The enhancement is 4.3–9.7% by doping 3 wt.% of SiO2 particles. Specific heat capacity was reduced when adding 5 and 7 wt.% of 30 μm SiO2 particles. Formation of sodium silicate is probably correlated to the reduction. Abstract: Several recent studies reported anomalous enhancement of specific heat capacity by doping minute concentration (e.g. 1 wt.%) of nanoparticles into the eutectic salt. In this work, silica particles with three different sizes and nano-sized silicon nitride and silicon carbide particles were dispersed in solar salt with particle concentrations of 0.5–7 wt.%. To prepare the composite material, a conventional two-step aqueous solution method was used and the drying approach was modified to suit large-scale production. The specific heat capacities of the composites, pure solar salt and particles were measured using differential scanning calorimetry in a temperature range of 300–400 ᵒC and the results were compared. Silicon nitride and silicon carbide nanoparticles have marginal effect on the specific heat capacity of solar salt over the examined concentration of 0.5–3 wt.%. The specific heat capacity of silica composites with 3 wt.% of silica were enhanced by 4.3–9.7% over that of the pure solar salt. However, when 5 wt.% and 7 wt.% of silica (30 μm) were dispersed, the specific heat capacity was reduced by 10.6% and 9%, respectively. Material characterization of the composite material proved the formation of sodium silicate due to reaction of silica and sodium nitrate, which is probably correlated to the reduction of specific heat capacity.